2019
DOI: 10.1038/s41598-019-52131-7
|View full text |Cite|
|
Sign up to set email alerts
|

Interactive Effects of Nitrogen-Fixing Bacteria Inoculation and Nitrogen Fertilization on Soybean Yield in Unfavorable Edaphoclimatic Environments

Abstract: The objective of this work was to evaluate the effect of nitrogen (N) fertilization and the biological nitrogen fixation efficiency in soybean crops grown in unfavorable environments (high temperature, low fertility, and areas with sandy soil). Six field experiments were conducted between 2015 and 2018. Two experiments were performed per year. They were conducted in two separate areas. One was previously covered with degraded pasture (post-pasture area). The other was previously used to plant soybean (post-soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…In this study, N-fertilized black oats reduced soybean nodulation (Figures 3A and B). In addition, N-fertilized soybean after fallow increased nodule number by 46%, compared to fallow, probably because a small supply of N was beneficial and did not harm BNF, as previously reported (Cordeiro & Echer, 2019). Xia et al (2017) report higher nodulation of soybeans with the addition of low levels (< 50 mg L -1 ) of nitrogen due to increased nitrogenase activity in soybean roots; however, high levels of mineral N (> 50 mg L -1 ) reduce nitrogenase activity and nodulation of soybeans.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…In this study, N-fertilized black oats reduced soybean nodulation (Figures 3A and B). In addition, N-fertilized soybean after fallow increased nodule number by 46%, compared to fallow, probably because a small supply of N was beneficial and did not harm BNF, as previously reported (Cordeiro & Echer, 2019). Xia et al (2017) report higher nodulation of soybeans with the addition of low levels (< 50 mg L -1 ) of nitrogen due to increased nitrogenase activity in soybean roots; however, high levels of mineral N (> 50 mg L -1 ) reduce nitrogenase activity and nodulation of soybeans.…”
Section: Resultssupporting
confidence: 80%
“…Xia et al (2017) report higher nodulation of soybeans with the addition of low levels (< 50 mg L -1 ) of nitrogen due to increased nitrogenase activity in soybean roots; however, high levels of mineral N (> 50 mg L -1 ) reduce nitrogenase activity and nodulation of soybeans. Additionally, in degraded post-pasture areas with low N stock in the soil, the application of up to 50 kg ha -1 of N does not reduce soybean nodulation (Cordeiro & Echer, 2019), as reported in this study (Figure 3A).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The greatest effects of this treatment were observed in fields without previous soybean cultivation [26]. Cordeiro and Echer [27] found that both mineral fertilization and soil inoculation increase N content in the soil, however the seed yield was clearly higher where the inoculant had been used. The lack of a clearly positive effect of seed inoculation on soybean yield can trigger some doubts as to whether the bacteria introduced proliferated, and if the inoculation was effective, or if environmental conditions and/or nitrogen fertilization did not disturb the development of symbiotic bacteria [7].…”
Section: Introductionmentioning
confidence: 92%